Crush performance of multifunctional hybrid foams based on an aluminium alloy open-cell foam skeleton - Duarte, Isabel (2020)
Multifunctional hybrid foams were developed and tested by combining aluminium alloy open-cell (OC) foam specimens with polymers, epoxy resin and silicone rubber. The rectangular OC foam specimens were impregnated with polymer, completely ﬁlling the voids. The aim of this work was to evaluate the eﬀect of the polymer presence in the voids of aluminium alloy OC foam specimens (varying their size, e.g. height to width ratio) on the crush performance of the resulting hybrid foams. Quasi-static and dynamic uniaxial compressive tests and infrared thermography were used to compare the behaviour of hybrid foams with conventional (unﬁlled) OC foam specimens. Results show an improvement of the compressive strength and energy absorption capacity of hybrid foams, especially when inﬁltrated with epoxy resin. The results show that the epoxy leads to higher capacity of speciﬁc energy absorption of the hybrid foams, while silicone leads to lower capacity of speciﬁc energy absorption in comparison to the OC foam specimens. The high energy absorption values of OC foams embedded with silicone are not enough to compensate for the mass increase due to the silicone ﬁller. The use of the polymers as a void ﬁller changes the typical layer-wise collapse mechanism of the OC foam. The silicone rubber causes a non-symmetric deformation, being much more complex and unstable in the case of the longer hybrid foams, which deform by buckling (lateral instability). The epoxy resin enforces a symmetric deformation by folding in the middle of the hybrid foams.